Acetylsalicylic acid in primary prevention among patients with arterial hypertension - A. V. Melekhov; E. E. Ryazantseva (Российский кардиологический журнал, 2013)
Arterial hypertension (AH) remains one of the most prevalent cardiovascular diseases (CVD) and is an important risk factor of severe, often fatal complications. CVD prevention in AH patients is a complex task, including not only blood pressure reduction, but also targeting additional risk factors. The HOT study was the first attempt to assess the effects of acetylsalicylic acid (ASA) on CVD risk in AH patients. It was shown that ASA reduced the risk of major cardiovascular events (non-fatal acute myocardial infarction (MI), non-fatal stroke, and cardiac death) by 15% (p=0,03). The risk of MI was reduced by 36% (p=0,02). In order to implement the HOT study results in the clinical practice, additional data analyses were performed, which demonstrated that ASA benefits were the most pronounced in patients with creatinine levels >150 mmol/l. The evidence from the HOT study, including the subgroup analysis results, has been included in the latest guidelines on AH management.